Extra Lessons and Academic Achievement of Learners among Urban Day High Density Secondary School Learners - Bukaliya, Richard (International Journal of Educational Studies, 2019)
This multiple case study was an analysis of the perceptions of teachers, parents, school inspectors and learners towards the role of extra lessons on the academic achievement of learners in three secondary schools in Chegutu Urban, Zimbabwe. The study was guided by the Incentive Theory of Motivation developed by Young (1936), which postulates that there are many reasons that drive people towards doing certain things. The study adopted the interpretivist paradigm that hinges on the premise that social meaning is created by interacting with various participants affected by a phenomenon it was rooted in the qualitative approach. Interviews, focus group discussions and document analysis were used to generate data. The results of the study show that extra lessons were used to improve learners` academic achievement. Extra lessons came in as a form of remediation for learners who failed to grasp concepts during the formal learning school hours. The lessons also enhanced slow learners? achievement and sustained gifted learners` academic levels through extension work. They helped learners in getting admission into institutions of higher learning. Due to the positive academic role of the extra lessons, it was recommended that there is need to take extra lessons seriously. Extra lessons could be used to make up for the time limitations in the urban day high density secondary schools where there is double sessioning. However, there is need to monitor the learners as they go away for the extra lessons to find out if, indeed, they are benefitting from them. Learners, who stand to benefit from the extra lessons, need to take into account that they should not wait for teachers to do virtually everything for them but rather use extra lessons for guidance on how they go about certain activities. Learners should do most of the activities through learner centred approaches, under the guidance of the extra lessons teachers. There is need for a legal frame work to operationalise the extra lessons. The Government of Zimbabwe could have extra lessons as a revenue base through which teachers practising extra lessons could have their extra remuneration from extra lessons taxed.